Indicadores de avaliaç\~ao subjetiva da suficiência da renda das famílias brasileiras: Um estudo com a Pesquisa de Orçamentos Familiares - Marcos Antonio Coutinho da Silveira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– The versions of 2002-2003 and 2008-2009 of the Household Budget Survey (POF) from the IBGE bring two questions on the subjective evaluation of Brazilian families about the sufficiency of their income. While the first question draws direct information on the degree of family's satisfaction with its monthly income, allowing to build from it a qualitative indicator of income sufficiency, the second question extracts information on the income value evaluated by the family as minimally necessary for covering their monthly expenses, allowing to build from it a quantitative indicator of income sufficiency, defined as the proportion to which the actual income exceeds that value. In looking into the empirical relationship between these two subjective indicators, the work can contribute not only to support these indicators as reliable measures of quality of life of Brazilian families in its material dimension, but also to explain the mismatch between quality objective and subjective indicators of life.
Keywords: I30; I31; I39; 330; life quality indicators; household income sufficiency